Epigenetic determinants of an immune-evasive phenotype in HER2-low triple-negative breast cancer - Andrés F. Bedoya-López; Sookyung Ahn; Miquel Ensenyat-Mendez; Javier I. J. Orozco; Sandra Iñiguez-Muñoz; Pere Llinàs-Arias; Samantha M. Thomas; Jennifer L. Baker; Peggy S. Sullivan; Jitin Makker; Julie B. Steele; Sunil M. Kurian; et al. (npj Precision Oncology)
Abstract Identifying molecular drivers in triple-negative breast cancer (TNBC) is crucial. While HER2-low expression predicts response to novel antibody-drug conjugates, its biological influence on TNBC biology is unknown. We performed a comprehensive multi-omics analysis, integrating genomic, epigenomic, transcriptomic, and proteomic profiling to characterize HER2-low TNBC. We generated genome-wide DNA methylation profiles from a multi-institutional cohort and integrated our data with three independent cohorts (TCGA, SCAN-B, I-SPY2). TNBC cases were categorized as HER2-zero (IHC 0) or HER2-low TNBC (IHC 1+/2+, ISH non-amplified). Among 506 patients (HER2-low, n = 288; HER2-zero, n = 218), HER2-low TNBC exhibited significantly lower tumor mutational burden (P = 0.02). Epigenetic analysis identified 5287 differentially methylated sites, with consistent hypermethylation of HLA genes in HER2-low tumors. Transcriptomic analyses revealed significant downregulation of genes enriched in immune response pathways (e.g., leukocyte activation, T-cell signaling) in HER2-low TNBC (adjusted P < 0.001). Immune cell deconvolution showed reduced immune cell infiltration in the HER2-low tumor microenvironment (P = 0.002). Higher expression of five immune-related genes, downregulated in HER2-low, correlated with improved relapse-free (HR = 0.52; P < 0.001) and overall survival (HR = 0.36; P < 0.001). HER2-low TNBC tumors display distinct molecular features compared to HER2-zero, imparting an immune-evasive phenotype. These findings provide critical insights into the unique biology of HER2-low TNBC, warranting further clinical investigation.